Chemical constituents of Garcinia eugenifolia and Garcinia nitida and their cytotoxic activities and antioxidant properties / Khong Heng Yen , Vivien Jong Yi Mian And Mizaton Hazizul Hasan - Heng Yen, Khong; Yi Mian, Vivien Jong; Hazizul Hasan, Mizaton (Research Management Institute (RMI), 2011)
There are several local Malaysian Garcinia species which have ethnobotanical uses but so far very few studies have been carried out to link these folkloric uses with the phytochemistry of these plant species. It would be interesting therefore, to develop phytochemical data of two such Sarawakian species which are Garcinia eugenifolia and Garcinia nitida which have not been reported before. Some species of Garcinia have been shown to possess interesting biological activities such as cytotoxic, antibacterial, antioxidant and anti-cancer activities. Leaves and stem bark samples of Garcinia eugenifolia and Garcinia nitida will be extracted and purified using standard protocols which involve the conventional extraction technique such as chromatographic methods. Analyses for structural elucidations of pure bioactive compounds will involve the usual spectroscopic techniques such as NMR, FTIR, UV and MS. The isolation and identifications of these natural products will lead the researchers to establish a profile of chemical and biological activities of the extract for standardisation and product development. The outcome of this project, which is a documentation of medicinal plants rich in active compounds, is for further investigation for their potential uses in drug development.